THE INFLUENCE OF LATIN AND GREEK ON MODERN MEDICAL TERMINOLOGY LINGUISTIC AND EDUCATIONAL PERSPECTIVES - Esanova Maftuna Bakhodirovna (Bright Mind Publishing, 2025)
Medicine is one of the most honorable, challenging, and lucrative occupations. Hippocrates, Avicenna, and Paracelsus were among the great ancient physicians who cared for people's health and established medicine as a profession, art, and science. They imparted their knowledge to their pupils. Latin and Greek have been the sole languages used for medical education and writing since the beginning of time. The sole language used by doctors worldwide for communication was Latin. Latin has long been the language of medicine and research. Latin was taught at many schools in England, France, and Italy. Established in the 13th century, the Sorbonne University in Paris taught biology and researched the anatomy, physiology, and treatment of various illnesses.
Keywords: Latin with Medical Terminology, Body Parts, Internal Organs, Medicinal Plants, and Medicinal Products and Preparations, systematizing medical knowledge and experience.